Efektivitas Media Pembelajaran Interaktif dalam Meningkatkan Minat dan Motivasi Belajar Siswa Sekolah Dasar - Ali, Amna; Dea Venica, Sheyvilda; Aini, Welsa; Faisal Hidayat, Akhmad (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
This study aims to analyze the effectiveness of interactive learning media in increasing elementary school students' interest and motivation to learn. Interactive learning media, such as animated videos, educational games, and simulations, present an engaging, participatory, and developmentally appropriate learning experience that is familiar to students. The research used a qualitative method with a literature review technique, which involved analyzing literature from various relevant sources, such as journals, books and research reports. The results of the study show that interactive media is able to increase student engagement in the learning process through active interaction with learning materials. In addition, it provides immediate feedback, which helps students understand their progress, boosts self-confidence and strengthens learning motivation. Interactive learning media also helps teachers create more dynamic and interesting learning. This research concludes that interactive media plays a significant role in creating an effective learning environment to increase students' interest and motivation.